Essays on economic integration - Chapman, Geoffrey S. (2019)
This thesis presents the findings of three empirical chapters related to economic integration. In the first of these chapters, we run a linear probability model (LPM) on a pooled sample of 106 countries, for the years 1960–2011; and on two sub-samples, one between 1960 and 1996 and the other between 1997 and 2011. This separation helps us determine whether the economic determinants of preferential trade agreements have changed, and our core result is that they have not. Second, for a panel of 180 countries and the years 1995–2012, we run Poisson regressions under three hypotheses, exploring whether integration lowers trade costs. We find that (i) forming trade agreements, (ii) deepening integration, and (iii) staying in trade agreements all significantly lowers trade costs. Our final empirical chapter explores the impact of regional integration on agricultural production in Sub-Saharan Africa using least squares estimates on a panel of 45 countries over the 1961–2014 time horizon. We find no effect of regional integration on agricultural production and, to help us understand why, we again turn to trade costs and Poisson estimation: for 44 SSA countries over the 1995–2012 time horizon, we find that regional integration has not lowered agricultural trade costs in Sub-Saharan Africa, but it has done so for the World.